Factors that Influence Traders' Income at Sanglah Market, West Denpasar District, Denpasar City - Wibawa, I Putu Agus Putra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Dauh Puri Klod Village was established based on the Decision of the Governor of Bali, designated as a Preparation Village to develop the administrative area of Dauh Puri. In terms of demographics, the population of Dauh Puri Klod Village is highly heterogeneous, consisting of various ethnicities, races, and religions. Generally, the residents are urban dwellers who are settled, with permanent residences and jobs. The data used in this study consists of primary data, which was obtained through direct interviews with informants and confirmed existing data. The sample size for this research included 78 respondents. The results of the multiple linear regression analysis indicate that capital, working hours, and business duration simultaneously have a positive and significant effect on the income of traders at Sanglah Market, West Denpasar District, Denpasar City. Additionally, capital, working hours, and business duration individually also have a positive and significant impact on traders' income at Sanglah Market, West Denpasar District, Denpasar City.